The Dual Influence: How Flash Sales and Fear of Missing Out (FOMO) Create a Synergistic Effect on Online Impulse Buying in TikTok Shop (A Study of Generation Z in Indonesia) - Vina Ardiana; Nuri Purwanto (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
The development of digital marketing strategies has driven changes in consumer behavior, particularly in the context of impulse buying on e-commerce platforms. The purpose of this study is to examine the influence of Flash Sales and Fear of Missing Out (FOMO) on impulse buying of fashion products on TikTok Shop among Generation Z in Jombang City. This study employs a quantitative approach with a sample of 100 respondents who are TikTok Shop users and have previously purchased fashion products online. Data analysis was conducted using multiple linear regression with the assistance of the SPSS application as the analytical tool. The results of the study indicate that Flash Sales have a positive and significant effect on Impulse Buying. In addition, FOMO also has a positive and significant effect on Impulse Buying. Thus, it can be concluded that these two variables are the main drivers of impulsive buying behavior among Generation Z in purchasing fashion products on TikTok Shop.